O google earth como ferramenta de ensino em geometria analítica. - Silva, Franciano Jose da (2019)
We are in the 21st century and technology is becoming more and more present in our lives and, as it should be no different, shows its reflexes in the classroom and in pedagogical practices. There are many software used as a teaching tool in many different subjects. This paper deals with the use of Google Earth software as a didactic tool in Mathematics classes, more specifically in Analytical Geometry. Its features allow to obtain the coordinates of points, to determine the distance between two points, to calculate perimeters and areas of polygons, etc., thus demonstrating their great potential in articulating and creating an enabling and motivating environment for the teaching-learning process of geometry. Analytical in high school since it allows to establish several connections of mathematics with different knowledge. At first, a significant number of students show some difficulty in establishing a connection between the basic topics of classroom content and thus not understanding basic concepts. The results obtained during the application of the activities proposed in this paper suggest that when opportunities and tools are developed to develop a sense of positioning in the local and regional environment, students tend to improve their conceptual knowledge as well as the ability to apply their respective knowledge. critical thinking skills and thus students’ learning becomes more meaningful and relevant to their everyday experiences.